2014
DOI: 10.1155/2014/643672
|View full text |Cite
|
Sign up to set email alerts
|

Design and Fabrication of Nanoscale IDTs Using Electron Beam Technology for High‐Frequency SAW Devices

Abstract: High-frequency Rayleigh-mode surface acoustic wave (SAW) devices were fabricated for 4G mobile telecommunications. The RF magnetron sputtering method was adopted to grow piezoelectric aluminum nitride (AlN) thin films on the Si3N4/Si substrates. The influence of sputtering parameters on the crystalline characteristics of AlN thin films was investigated. The interdigital transducer electrodes (IDTs) of aluminum (Al) were then fabricated onto the AlN surfaces by using the electron beam (e-beam) direct write lith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…It was also reported that when the sputtering pressure increased, the collision between sputtering particles and Ar ions led to the formation of AlN (100) films [ 64 ]. Both observations have been reported by many researchers in Table 2 such as in references [ 17 , 22 , 28 , 35 , 39 , 41 , 45 ].…”
Section: Compilation Of Recipes and The Roles Of The Sputtering Pasupporting
confidence: 71%
See 2 more Smart Citations
“…It was also reported that when the sputtering pressure increased, the collision between sputtering particles and Ar ions led to the formation of AlN (100) films [ 64 ]. Both observations have been reported by many researchers in Table 2 such as in references [ 17 , 22 , 28 , 35 , 39 , 41 , 45 ].…”
Section: Compilation Of Recipes and The Roles Of The Sputtering Pasupporting
confidence: 71%
“…For each parameter, selected works that investigate its effect will be mentioned. In addition to using the works that were already summarized in Table 2 , i.e., references [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ], we also highlight additional articles that are not included in that table i.e., references [ 63 , 64 , 65 , 66 , 67 , 68 , 69 , …”
Section: Compilation Of Recipes and The Roles Of The Sputtering Pamentioning
confidence: 99%
See 1 more Smart Citation
“…The global systems for mobile communication could be classified into four types of systems, GSM850/GSM900 band, DCS (GSM1800), WCDMA, and LTE. Thence, several acoustic devices were investigated for high frequency band such as nano-scaled surface acoustic wave (SAW) resonator (1) , thin-film bulk acoustic resonator (TFBAR) (2,3) and SMR.…”
Section: Introductionmentioning
confidence: 99%
“…as it exhibits efficient piezoelectric and dielectric properties, high thermal stability, as well as low dielectric loss tangent and high signal to noise ratio [35][36][37]. Additionally, no poling or stretching is needed [38].…”
mentioning
confidence: 99%